International journal of mental health systems: a bibliometric study - Harry Minas; Alexandra Wright; Mengxue Zhao; Ritsuko Kakuma (2014)
The International Journal of Mental Health Systems (IJMHS) was launched in August 2007 and has recently been given a formal impact factor. This study uses bibliometric indicators to review the performance of the Journal against its original stated objectives and aspirations. All articles published in IJMHS since publication commenced were included (n = 158). Selected bibliometric measures indicating Journal productivity, author affiliation, impact, geographic reach, and international collaboration were utilised. IJMHS published 158 articles in seven volumes over six years. Articles with three to five authors constitute the dominant authorship pattern, and authors' affiliations are varied. IJMHS has received an impact factor of 1.06 from Thomson Reuters, and the SCImago Journal Ranking shows IJMHS to be well positioned in the four categories in which it is listed, including in comparisons with well-established BMC journals that have similar scientific interests. Geographic authorship patterns show contributions from a large number of countries, including many low- and middle-income countries. Manuscript submissions from a wide range of countries, including low- and middle-income countries, are mostly from academic institutions. Authors from some geographic areas of the world are significantly under-represented. The calculation of an impact factor and encouraging rankings on the SCImago Journal Rank index are expected to lead to increased submission of high quality manuscripts. The performance of IJMHS over the first six years is promising, and the Journal is on the way to achieving the aims set out in the inaugural Editorial. IJMHS will continue to enhance its current impact through a number of new initiatives, including the introduction of thematic series and a broader range of article categories.